Correction: Split-anion solvent extraction of light rare earths from concentrated chloride aqueous solutions to nitrate organic ionic liquids. Issue 72 (15th December 2020) - Regadío, Mercedes; Vander Hoogerstraete, Tom; Banerjee, Dipanjan; Binnemans, Koen
Abstract : Correction for 'Split-anion solvent extraction of light rare earths from concentrated chloride aqueous solutions to nitrate organic ionic liquids' by Mercedes Regadío et al., RSC Adv., 2018, 8, 34754–34763, DOI: ; 10.1039/c8ra06055j .